The interferon-inducible double-stranded RNA-activated protein kinase self-associates in vitro and in vivo. - Patel, R C (1995)
The interferon-inducible double-stranded (ds) RNA-activated protein kinase (PKR) exhibits antiviral, anticellular, and antitumor activities. The mechanisms of its enzymatic activation by autophosphorylation and of the observed transdominant inhibitory phenotype of enzymatically inactive mutants have invoked PKR dimerization. Here we present direct evidence in support of PKR-PKR interaction. We show that radiolabeled PKR can specifically interact with matrix-bound unlabeled PKR in the absence of dsRNA. The self-association activity resides, in part, in the N-terminal region of 170 residues, which also constitutes the dsRNA-binding domain (DRBD). DRBD can bind to matrix-bound PKR or to matrix-bound DRBD. Dimerization of DRBD was directly demonstrated by chemical crosslinking. Affinity chromatography and electrophoretic mobility supershift assays demonstrated that mutants that fail to bind dsRNA can still exhibit protein-protein interaction. The PKR-PKR interaction could also be observed in a two-hybrid transcriptional activation assay in mammalian cells and consequently is likely to be an important feature of PKR activity in vivo.